Digital Storytelling as a Communication Strategy of Virtual Peasant’s Resistance - Aprilianti Pratiwi; Dimas Aryalasa Nugroho; Yolanda alentia (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2022)
The high number of land conflicts will make farmers continue to carry out resistance movements. Now along with the development of technology, the activists of the peasant resistance movement use the internet to fight. This is what activists do. They help STTB Farmers (Serikat Tani Telukjambe Bersatu) in channeling their aspirations to reclaim land rights that have been snatched away by a corporation. The activist uploaded videos of the act of burying the STTB Farmer's self, which is a form of resistance to the dominant narrative. This activity of documenting and uploading it to an internet channel is called digital storytelling. The purpose of this study was to analyze digital storytelling which was used as a communication strategy for the STTB virtual farmer resistance. This research uses CMC (Computer Mediated Communication) theory with digital storytelling analysis. The results showed that there were a number of digital storytelling elements in the STTB farmer's self-burying video, namely Point of View, The Gift of Your Voice, and The Power of The Soundtrack. Even though this video of the STTB farmer's self-burying is made and presented in a simple way, it is precisely the simplicity that is its strength. This video is made naturally without any made-up scenes by the characters in this video, namely farmers and land conflict activists.